Pesawat Terbang Tanpa Awak (PTTA) sebagai Pengembangan Media Sistem Informasi Geospasial - Diyan Parwatiningtyas (Universitas Indraprasta PGRI Jakarta, 2019)
As we know, Indonesia has a dynamic structure of the earth's surface layer. This topographic differences level was results in land variations and it impacts on the material contained in it. This certainly will growth an enrich amount of natural land resources and the quality of plant vegetation and the sea. All of them are natural resources that are beneficial for human survival and the other habitats. To monitoring its management from the surface, we need a method that serves to inform the potential region conditions, one of them is the Geospatial Information System (GIS). Generally, taken data for GIS could be obtained through aerial photography of satellite images. However, the results are less accurate, so that, we look for the other alternatif instruments, which could made a GIS map better, using the design of unmanned aircraft vehicle (PTTA) or commonly known as drones. For now, Unmanmed Aircraft Vehicle is a currently technology which that is growing rapidly. On this occasion, the author will introduce UAV technology that can be designed by itself according to needed, and could be able to answer every problems in which related to image mapping from geospatial information systems.